Correlation of buccal micronucleus with disease activity score using buccal micronucleus cytome analysis (BMCA) in systemic lupus erythematosus - Khalil Assiri; Mohammad Shahul Hameed; Ali Azhar Dawasaz; Eman Alamoudi; Alhussain Mohammad Asiri; Hitesh Vij; Muhammed Ajmal (Wolters Kluwer Medknow Publications, 2020)
Background: A disease activity score obtained by using systemic lupus erythematosus disease activity index (SLEDAI) has traditionally been a reliable method to assess the SLE status of patients. More recently, a buccal micronucleus cytome assay (BMCA) has been developed for use as a biomarker of DNA damage in patients with SLE. There has been a very limited number of studies pertaining to the oral lesions in Arab population suffering from SLE in Asir region. Hence, it became utmost important to study epidemiological data of oral mucosal lesions in SLE patients. Distribution of oral lesions in SLE patients could also be helpful in better management of oral complications. Aim: The aim of this study was to determine the existence of a correlation between SLEDAI score and the degree of micronuclei (MN) formation using BMCA. Materials and Methods: After thorough oral examination of adult Saudi SLE patients of Asir hospital and that of healthy control subjects, the subjects underwent BMCA from normal unaffected bilateral buccal mucosae. Results: Pearson's correlation test showed that MN count did not significantly correlate with either disease activity or duration of SLE. Conclusions: Controlled state SLE does not lead to a significant increase in MN formation. Thus, the occurrence of premalignant lesions in the oral cavity could be minimized using proper management protocols.